Red Clay Suite - Jeffers, Honoree Fanonne, 1967- (Book collections on Project MUSE., 2007)
In her third book of poems, Honoree Fanonne Jeffers expresses her familiarity with the actual and imaginary spaces that the American South occupies in our cultural lexicon. Her two earlier books of poetry, The Gospel of Barbecue and Outlandish Blues, use the blues poetic to explore notions of history and trauma. Now, in Red Clay Suite, Jeffers approaches the southern landscape as utopia and dystopia-a crossroads of race, gender, and blood. These poems signal the ending movement of her crossroads blues and complete the last four "bars" of a blues song, res.